Hubungan Antara Media Sosial dengan Kunjungan Pasien di Rumah Sakit: A Scoping Review - Fawzia Haura Fathin; Zahroh Shaluhiyah (Malahayati Nursing Journal, 2026)
ABSTRACT Social media platforms enable rapid information dissemination and direct communication with patients and communities worldwide. This encourages healthcare providers to integrate them for health promotion, brand building, and professional networking. The objective of this research is to conduct a comprehensive review of the scholarly works concerning leveraging social media for enhancing hospital patient traffic. This scoping review utilized data from EBSCO host, Oxford, PubMed, and Scopus. The inclusion criteria were publications from the last eight years, available in full-text, open access, English-language, and of the article document type. The keywords used combined terms for social media (e.g., "Social Media Marketing" OR "Social Media Strategy" OR "Health Media" OR " Social Media" OR "Hospital Instagram" OR "Healthcare Facebook" OR "Hospital TikTok" OR "Hospital YouTube") AND ("Patient Visits" OR "Patient Attendance" OR "Hospital Visits" OR "Outpatient Visits" OR "Patient Purchase" OR "Patient Appointment" OR "Patient Volume" OR "Hospital Utilization") AND ("Hospital" OR "Healthcare Facility" OR "Medical Center").This scoping review of 15 studies reveals social media's potential to increase hospital patient visits, but its impact is not direct. Effectiveness hinges on building brand awareness, trust, and positive patient experiences as key mediators. The most successful strategies use educational content and collaborations with local professionals. However, factors like prior experience and geographic access often outweigh social media's influence, positioning it as one component within a broader marketing strategy. Keywords: Social Media, Marketing, Hospital, Patient Visits.